KOMUNIKASI ANTARPRIBADI GURU TERHADAP SISWA BERKEBUTUHAN KHUSUS DALAM MEMBENTUK KEPERCAYAAN DIRI SISWA DI SEKOLAH LUAR BIASA NEGERI (SLBN) DESA SANSARINO KABUPATEN TOJO UNA-UNA - Ningsih, Fitriani Puspa; Fadhliah; Mohamad, Nur Santi M.; Shanty, Nursanti M.Mohamad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2022)
State Extraordinary School (SLBN) Sansarino Village, Tojo Una-Una Regencyis a Special School which is devoted to children with special needs to develop knowledge and ways to socialize with others so that they can better understand self-confident. Students with special needs are also students who need special attention because they need guidance and education in living their lives. The need for inclusion, the need for control and the need for affection shown by the teacher to students greatly helps the teacher's teaching and learning process. Interpersonal communication at the SLBN of Sansarino Village, verbally and non-verbally, was carried out well and the teachers also made efforts to increase self-confidence in Children with Special Needs. Such as efforts to present a comfortable and fun teaching and learning process for students, provide motivation to students, increase the competitive spirit among students, not discriminate against weak children, provide training to students to increase self-confidence. Students are able to control their behavior well in daily life, can adapt and interact, have a sense of mutual concern, a sense of social solidarity, tolerance for each other so that there is no sense of being left out. Because they have a sense of mutual need, kinship and respect for one another.